Coastal Guardians: The Crushing Depths - Book 2 - Pettrey, Dani (Minneapolis, Minnesota : Bethany House Publishers, 2020)
"When an accident claims the life of an oil-rig worker off the North Carolina coast, Coast Guard investigators Rissi Dawson and Mason Rogers take on the case. Mounting evidence shows the death may have been murder, and they must race to discover the killer's identity before he finds them first"--
Keywords: Murder -- Fiction. -- Investigation; Oil well drilling rigs -- Fiction; North Carolina -- Fiction; Detective and mystery fiction; Christian fiction